Living with a SEAL : 31 days training with the toughest man on the planet - Itzler, Jesse (Center Street, 2015)
Entrepreneur and one-time rapper (under the name Jesse Jaymes) Jesse Itzler's life is bold and risky by design, which in turn has brought him plenty of rewards. Feeling that his life has begun to run on autopilot, Itzler hires a Navy SEAL to live with and train him for a month, and what ensues is both hilarious and inspirational.